Aspectos da eficiência e eficácia dos mecanismos de informação nas interações com o consumidor residencial - Bomfim, Christina de Andrade Meirelles (2003)
This paper covers the question about efficiency and efficacy of the means of information used by the agents who operate in the electrical energy market Utilities, Concessionaries, Regulating Organ, and Regional Agencies, focusing on the Group B Residential Consumer. The analysis herein developed, aims at diminishing the asymmetrics in information, which exists on the market and comply with the objectives of the utility in efficiency with regard to the consumer. It is also the intention of this paper to contribute to more efficient action on the part of the regulating organ whose complementary function is to keep the market agents and the public as a whole, informed of the regulations established in the electric energy supply contract. To this end, the difficulties faced by this type of consumer in interpreting and understanding the legal terms the Contract, as well as the means of communication, are initially appraised. Generally speaking, this class of consumer does not dispose of legal help to clarify and explain rights and obligations, as compared to the Group A Industrial Consumer. Considering that a unsatisfied consumer, due to ignorance, erroneous interpretation or lack of adequate attention, may generate complaints, the guideline adopted for the methodology of research is to investigate the attention given to the consumer, observation of the types of complaints made to the responsible agents in charge receiving such complaints, and the frequency thereof. A diagnosis of the actual situation is made thereafter, indicating investment requirements in the quality of the service rendered, in the information furnished in the service contract/invoice and in the comprehension of consumer complaints. In conclusion, a comparative analysis is made of the complaints classification formats adopted in by Agência Nacional de Energia Elétrica ANEEL/Agência Estadual de Regulação de Serviços Públicos de Energia, Transportes e Comunicações da Bahia AGERBA/Companhia de Eletricidade do Estado da Bahia - COELBA, with suggestions for adaptation and unification of the classification formats.